Aortic stiffness, blood pressure progression, and incident hypertension - Kaess, Bernhard M; Rong, Jian; Larson, Martin G; Hamburg, Naomi M; Vita, Joseph A; Levy, Daniel; Benjamin, Emelia J; Vasan, Ramachandran S; Mitchell, Gary F (JAMA : the journal of the American Medical Association, 2012)
Vascular stiffness increases with advancing age and is a major risk factor for age-related morbidity and mortality. Vascular stiffness and blood pressure pulsatility are related; however, temporal relationships between vascular stiffening and blood pressure elevation have not been fully delineated. To examine temporal relationships among vascular stiffness, central hemodynamics, microvascular function, and blood pressure progression. Longitudinal community-based cohort study conducted in Framingham, Massachusetts. The present investigation is based on the 2 latest examination cycles (cycle 7: 1998-2001; cycle 8: 2005-2008 [last visit: January 25, 2008]) of the Framingham Offspring study (recruited: 1971-1975). Temporal relationships among blood pressure and 3 measures of vascular stiffness and pressure pulsatility derived from arterial tonometry (carotid-femoral pulse wave velocity [CFPWV], forward wave amplitude [FWA], and augmentation index) were examined over a 7-year period in 1759 participants (mean [SD] age: 60 [9] years; 974 women). The primary outcomes were blood pressure and incident hypertension during examination cycle 8. The secondary outcomes were CFPWV, FWA, and augmentation index during examination cycle 8. In a multivariable-adjusted regression model, higher FWA (β, 1.3 [95% CI, 0.5-2.1] mm Hg per 1 SD; P = .002) and higher CFPWV (β, 1.5 [95% CI, 0.5-2.6] mm Hg per 1 SD; P = .006) during examination cycle 7 were jointly associated with systolic blood pressure during examination cycle 8. Similarly, in a model that included systolic and diastolic blood pressure and additional risk factors during examination cycle 7, higher FWA (odds ratio [OR], 1.6 [95% CI, 1.3-2.0] per 1 SD; P < .001), augmentation index (OR, 1.7 [95% CI, 1.4-2.0] per 1 SD; P < .001), and CFPWV (OR, 1.3 [95% CI, 1.0-1.6] per 1 SD; P = .04) were associated with incident hypertension during examination cycle 8 (338 cases [32%] in 1048 participants without hypertension during examination cycle 7). Conversely, blood pressure during examination cycle 7 was not associated with CFPWV during examination cycle 8. Higher resting brachial artery flow (OR, 1.23 [95% CI, 1.04-1.46]) and lower flow-mediated dilation (OR, 0.80 [95% CI, 0.67-0.96]) during examination cycle 7 were associated with incident hypertension (in models that included blood pressure and tonometry measures collected during examination cycle 7). In this cohort, higher aortic stiffness, FWA, and augmentation index were associated with higher risk of incident hypertension; however, initial blood pressure was not independently associated with risk of progressive aortic stiffening.